Virtual Reality and BIM Methodology as Teaching- Learning Improvement Tools for Sanitary Engineering Courses - Rossado Espinoza, Verónica Paola (2021)
Virtual Reality (VR) is often used to describe a 3D environment wherein objects and images of the real world are simulated through technology. In architectural or civil engineering, the design process with 2D planes could lead to error owing to misinterpretation in the visualization of elements. The civil engineering program of a university in Lima, Peru, mandates the teaching of the building information modeling (BIM) methodology in all the courses, thereby allowing the students to learn about the organization and optimization of projects from the design phase to construction phase. The engineering students are required to manage many variables with the BIM methodology, especially in mechanical, electrical, and plumbing systems. Nevertheless, the teaching method of BIM could be enriched by analyzing 3D project models using VR. Whereas BIM organizes and optimizes a project through a 3D model, VR can introduce the user to a model that is very close to the reality, thereby improving the interpretation and analysis of the details. This study contributes to the implementation of a plumbing engineering course under a civil engineering program. The proposed methodology was applied in an experimental group of undergraduate students, and the test results obtained were compared with those of a control group that had used a traditional approach. The results of this study show that students, by using the VR–BIM method proposed, can successfully visualize the accessories and recognize a satisfactory design in a creative and innovative manner.